When one door closes: a qualitative exploration of women's experiences of access to sexual and reproductive health services during the COVID-19 lockdown in Nigeria - Babatunde Adelekan; Lanre Ikuteyijo; Erika Goldson; Zubaida Abubakar; Oluwatomi Adepoju; Olaitan Oyedun; Gbenga Adebayo; Andat Dasogot; Ulla Mueller; Adesegun O. Fatusi (BMC, 2024)
Abstract Background COVID-19 pandemic widely disrupted health services provision, especially during the lockdown period, with females disproportionately affected. Very little is known about alternative healthcare sources used by women when access to conventional health services became challenging. This study examined the experiences of women and adolescent girls regarding access to sexual and reproductive health (SRH) services during the COVID-19 lockdown in Nigeria and their choices of alternative healthcare sources. Methods The study sites were two northern states, two southern states, and the Federal Capital Territory. Qualitative data were obtained through 10 focus group discussion sessions held with married adolescents, unmarried adolescents, and older women of reproductive age. The data were transcribed verbatim and analysed using a thematic approach and with the aid of Atlas ti software. Results Women reported that access to family planning services was the most affected SRH services during the COVID-19 lockdown. Several barriers to accessing SRH services during COVID-19 lockdown were reported, including restriction of vehicular movement, harassment by law enforcement officers, fear of contracting COVID-19 from health facilities, and fear of undergoing compulsory COVID-19 tests when seeking care in health facilities. In the face of constrained access to SRH services in public sector facilities during the COVID-19 lockdown, women sought care from several alternative sources, mostly locally available and informal services, including medicine vendors, traditional birth attendants, and neighbours with some health experience. Women also widely engaged in self-medication, using both orthodox drugs and non-orthodox preparations like herbs. The lockdown negatively impacted on women's SRH, with increased incidence of sexual- and gender-based violence, unplanned pregnancy resulting from lack of access to contraceptives, and early marriage involving adolescents with unplanned pregnancies. Conclusion COVID-19 negatively impacted access to SRH services and forced women to utilise mostly informal service outlets and home remedies as alternatives to conventional health services. There is a need to ensure the continuity of essential SRH services during future lockdowns occasioned by disease outbreaks. Also, community systems strengthening that ensures effective community-based health services, empowered community resource persons, and health-literate populations are imperative for overcoming barriers to healthcare access during future lockdowns.